Research Self-Efficacy: A Meta-Analysis - Livinti, Raluca; Gunnesch-Luca, George; Iliescu, Dragos (Educational Psychologist, 2021)
Research self-efficacy represents the adaptation of the social cognitive concept of self-efficacy to the field of academic and scientific research and is one of the best predictors of successfully engaging in research activities. The current meta-analysis focuses on the relationship between research self-efficacy and 14 other relevant variables suggested by Social Cognitive Career Theory and analyzes 85 published and unpublished studies conducted between 1989 and 2020 (n = 17,754, 209 effect sizes). The results indicate large associations between research self-efficacy and interest in research, research identity, intention/goals to pursue a career in research, research productivity, attitudes toward research, research training environment, and working alliance with the advisor, moderate associations with research outcome expectations, Holland’s investigative interests, research anxiety, and research mentoring experiences, as well as a small association with year in doctoral studies. There is no significant relationship between research self-efficacy and two other variables, gender and age of participants. Our findings help educators by showing ways through which to increase research self-efficacy in order to improve research training and career outcomes; the results suggest that effective routes for educators are the selection of students who have investigative vocational interests, an active control of possible research anxieties, development of a strong research-oriented culture in the research group and the development of a mentoring and transformational relationship with their trainee

Secular Changes in Personality: An Age-Period-Cohort Analysis - Gunnesch-Luca, George; Ion, Andrei; Petre, Dan; Iliescu, Dragos (Journal of research in personality, 2022)
There has been a surge in media interest regarding the generational effects on the distribution and structure of personality traits. This article examines time and generational effects on the Five Factor personality traits. Hierarchical Age-Period- Cohort Modeling (HAPC) was deployed on a sample of 30,722 participants assembled from pooled repeated cross-sectional data collected between 2006 and 2018. After controlling for both age and period effects no generation-related effects in personality traits (both aggregate and facet levels) were detected. Our findings imply that broad societal changes delineating various “generations” exert a minor influence over the distribution of personality traits in the general populatio

Time and Generational Changes in Cognitive Performance in Romania - Gunnesch-Luca, George; Iliescu, Dragos (Intelligence, 2020)
The Flynn effect describes sustained gains in cognitive performance that have been observed in the past century. These improvements are not evenly distributed, with strong variations across regions or groups. To this effect, we report time and generational trends in IQ development in Romania. Using pooled repeated cross-sectional data ranging from 2003 to 2018 (N = 12,034), we used Hierarchical Age-Period-Cohort Models (HAPC) on data measured with the Multidimensional Aptitude Battery II. The results show an increase in measured performance of about one third of an IQ point per year, mainly driven by individual level effects and with additional variance attributable to generational (cohort) and period effect
Keywords: Flynn effect; Intelligence; Romania; Hierarchical Age-Period-Cohort